Keep your Liver Happy during Pregnancy! (Homoeopathy for All, 2024)
Most of the changes your body  undergoes during pregnancy  are healthy and expected. Some  effects of pregnancy may cause  you discomfort, but many of  these common discomforts can  be prevented relieved by simple  measures. However, you should be  aware of symptoms that are not usual  and may indicate a serious problem  that requires careful monitoring  or special treatment during your  pregnancy. These conditions include  diabetes, hypertension, thyroid  disorders, kidney disorders and liver  disorders. Liver disorders, though  not very common during pregnancy  need special attention and care as  they can pose a risk to you or your  foetus. The common liver disorders  that can affect a woman during  pregnancy are mentioned here with  their causes, symptoms, prevention  and management.
Keywords: pregnant woman; itching